Association between long-term static postures exposure and musculoskeletal disorders among university employees: A viewpoint of inflammatory pathways - Dong, Yidan; Jiang, Ping; Jin, Xu; Jiang, Nanyu; Huang, Wenchu; Peng, Yu; Shen, Yuhong; He, Lihua; Forsman, Mikael; Yang, Liyun (Frontiers in Public Health, 2022)
Background Musculoskeletal disorders (MSDs) are critical occupational and social problems. With the improvement of production mechanization and automation, and the widespread application of computers, more occupations are exposed to static postures and load. This study explored the role of inflammation in the association between static postures exposure and MSDs. Methods This study adopted a prospective nested case-control design in which 66 lower back MSDs cases and 66 healthy controls were selected from a cohort study of university employees. The personal information, postural load, musculoskeletal symptoms, pressure pain thresholds (PPTs), and inflammatory cytokines were collected. Logistic and linear regressions were used to investigate the association among postural load, inflammatory cytokines, and lower back MSDs. Mediation analysis was used to calculate the mediation effect. Results The results of logistic and linear regressions showed that postural load and inflammatory cytokines were positively associated with lower back MSDs (P < 0.05), and postural load was positively associated with inflammatory cytokines (P < 0.05). Further, mediation analysis showed that the mediation effect of postural load on the lower back MSDs through TNF-α was 0.073 (95%CI: 0.025–0.128), and the mediation effect of posture load on the lower back MSDs through IL-6 was 0.098 (95%CI: 0.041–0.179), respectively. Conclusion Static postures were associated with the occurrence of MSDs through inflammatory cytokines, and low-level inflammation may be a critical early event in the generation of MSDs. This study may help bridge the gap of potential mechanisms linking static postures to increased risks of MSDs, and provide new evidence for targeted protection against the global increasing MSDs.